2010
DOI: 10.2106/jbjs.i.00508
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Long Gamma Nail with the Sliding Hip Screw for the Treatment of AO/OTA 31-A2 Fractures of the Proximal Part of the Femur

Abstract: When compared with the long gamma nail, the sliding hip screw should remain the gold standard for the treatment of AO/OTA 31-A2 fractures of the proximal part of the femur because it is associated with similar outcomes with less expense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
179
3
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 218 publications
(199 citation statements)
references
References 19 publications
12
179
3
5
Order By: Relevance
“…There continues to be controversy regarding the optimum treatment of intertrochanteric fractures [3,5,25,27,28,30,32]. Several large prospective randomized trials have directly compared sliding hip screws and contemporary cephalomedullary nail constructs and have shown similar outcomes between the two techniques [3,27,28,30,34].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There continues to be controversy regarding the optimum treatment of intertrochanteric fractures [3,5,25,27,28,30,32]. Several large prospective randomized trials have directly compared sliding hip screws and contemporary cephalomedullary nail constructs and have shown similar outcomes between the two techniques [3,27,28,30,34].…”
Section: Resultsmentioning
confidence: 99%
“…There continues to be controversy regarding the optimum treatment of intertrochanteric fractures [3,5,25,27,28,30,32]. Several large prospective randomized trials have directly compared sliding hip screws and contemporary cephalomedullary nail constructs and have shown similar outcomes between the two techniques [3,27,28,30,34]. The most recent Cochrane review on the topic [28] concluded that the sliding hip screw is the superior construct for treatment of intertrochanteric fractures because of the decreased rate of surgical complications compared with cephalomedullary nails, but additional studies are necessary to determine whether newer designs of cephalomedullary nails avoid the complications of older models, such as those used for periimplant fracture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations